The influence of two bar warp-knitted structure on the fabric tensile stress relaxation Part I: (reverse locknit, sharkskin, queens' cord). Issue 4 (2nd April 2016) - Hashemi, Nasrin; Asayesh, Azita; Jeddi, Ali Asghar Asgharian; Ardakani, Toba
Abstract : Time-dependent mechanical behavior of textiles has particular importance. One of such behaviors is the stress relaxation. If a fabric is under tension over a period of time, some of the stresses in it will be relieved. During the manufacture and application of clothing and footwear, materials experience various long-lasting deformations, and relaxation process in materials arises. For example, if medical pressure garments such as compression stockings are under tension over a long period of time, some of their stresses will be relieved, with a consequent reduction in the skin and garment interfacial pressure. Thus, with theoretical and experimental study of the factors affecting stress relaxation, the ability to design and produce appropriate clothes will be increased. The aim of this study was to investigate the effect of fabric structure on the stress relaxation of two bar warp-knitted fabrics (reverse locknit, sharkskin, queens' cord), as well as to find the effect of strain value and loading direction on the stress relaxation of the fabrics. The results reveal that the fabric structure, strain, and loading direction are important factors affecting the stress and stress relaxation percent of the fabrics. By increasing the strain and the length of underlap in the back guide bar, stress will be increased, but stress relaxation percent will be decreased. Also, stress relaxation percent in wale direction is more than course direction for reverse locknit and sharkskin3, but this is reversed for sharkskin4 and queens' cord. Finally, among the mechanical models used to describe the stress relaxation behavior of the fabrics, three-component Maxwell's model with parallel-connect nonlinear spring showed the best agreement with the experimental relaxation curve of the analyzed fabrics.